(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
The problem of portable water supply has become an issue of global concerned as governments all over the world are trying to make house-holds water accessible to all as easier as possible to meet the challenges for sustainable development goals. This research has been conducted to determine the people’s perception on domestic water supply situation in Kano metropolis, Northwestern Nigeria. A self-designed questionnaire developed and distributed to the subjects using stratified sampling technique, and the data obtained has been presented in frequency and percentage. The results obtained revealed that, there is a scarcity of portable water supply to households in Kano metropolis. The problem emanated from lack of pipe-borne water which necessitated the dependence of the house-holds water supply on vendors that obtained water from boreholes and some hand-dug wells lacking proper hygienic practices. More so, the respondents were willing to pay for pipe borne water delivery, yet, they depend on vendors as their major water suppliers as alternatives. The unhygienic practices of the vendors and water sources posed threat to public health concerned.